Investigating risk of self-harm and suicide on anniversaries after bereavement by suicide and other causes: a Danish population-based self-controlled case series study - Alexandra Pitman; Yanakan Logeswaran; Keltie McDonald; Julie Cerel; Gemma Lewis; Annette Erlangsen (Epidemiology and Psychiatric Sciences, 2023)
Abstract Aims To investigate mechanisms of suicide risk in people bereaved by suicide, prompted by observations that bereaved people experience higher levels of distress around dates of emotional significance. We hypothesised that suicide-bereaved first-degree relatives and partners experience an increased risk of self-harm and suicide around dates of (i) anniversaries of the death and (ii) the deceased’s birthday, compared with intervening periods.